Model prediksi kejadian demam berdarah dengue di kota yogyakarta bagian utara (zona musim 138) tahun 2010-2016 - Dedik Sulistiawan; Lutfan Lazuardi (Berita Kedokteran Masyarakat (BKM), 2018)
Use of a combined surveillance and meteorological data for predicting dengue hemorrhagic fever in YogyakartaPurposeThis study aimed to predict the incidence of dengue hemorrhagic fever using meteorological data such as rainfall, rainy days, air temperature, humidity, and dengue hemorrhagic fever surveillance data month by month in Northern Yogyakarta Municipality (Climatic Zone 138) through 2010-2016.MethodThis research was a descriptive study with a predictive design with temporal approach. This research processed secondary data of DHF incidence from Yogyakarta Municipality Health Office and climate variables from Meteorology Climatology and Geophysics Agency (BMKG) Yogyakarta from 2010 to 2016. Data were analyzed with univariate tests and presented in frequency distribution, bivariate analysis was performed using  Pearson/ Spearman correlation tests, and multivariate analysis used Poisson regression, negative binomial regression, and generalized poisson regression tests.ResultsDHF incidence in Northern Yogyakarta Municipality (Climatic Zone 138) was associated with meteorological factors in the same month up to 3 months earlier. Predictors of DHF case were dengue incidence of previous month, rainfall 2 months earlier, current temperature, and relative humidity of the previous month.ConclusionThe best prediction model of DHF incidence in Northern Yogyakarta Municipality (Climatic Zone 138) was a combination of surveillance and meteorological data. It is necessary to develop an awareness system of DHF incidence with meteorological database and surveillance in order to control the incidence of DHF in Yogyakarta Municipality.